STAFFING OF RUSSIAN ARMY OFFICERS: EDUCATION QUALIFICATION (1900-1914) - V. N. Suryaev (Гуманитарные и юридические исследования)
The development of the military-political situation in the world clearly demonstrates the importance of further enhancing the combat potential of the Armed Forces. A factor of prime importance in this case is to ensure that the level of education of oficers, which will allow them to meet their professional duties in any environment. In this regard, the study of the experience of command staff training in a complex international situation, the beginning of the twentieth century, is very important. This article is devoted to the consideration of measures aimed at improving the training of future oficers in the military system of secondary education in the Russian army in the period preceding the First World War.